A scheme for inviscid compressible flow, considering a gas in thermo-chemical equilibrium - Saldía, Juan Pablo (2015)
A finite volume scheme for the solution of the unsteady 1D Euler equations, considering the working gas in thermo-chemical equilibrium, is presented. To achieve total variation diminishing (TVD) properties in the numerical scheme, a technique proposed by the co-authors, based on the use of different limiter functions in each wave of the Riemann problem, is applied. By proper selection of the limiter functions, the unwanted effects of the numerical viscosity on the capture of contact discontinuities are reduced, but without losing robustness in shock waves resolution. With the aim of evaluating the developed numerical scheme, results obtained solving several Riemann problems, specially selected for this specific purpose, are presented.